Carbon Stock Estimation of Bandeshwori Community Forest, Bhaktapur, Nepal (Padmakanya Journal of Science and Technology, 2025)
Community forestry in Nepal has contributed to forest conservation, expansion of greenery, and climate mitigation through carbon sequestration. However, the lack of baseline data on carbon stocks has hindered the quantification of the carbon sequestration potential of such forests. This study conducted at Bandeshwori Community Forest, Bhaktapur estimated the total carbon stock of the forest. Standard 23 nested circular plots, each measuring 250 m2 were established for field sampling. The diameter at breast height (DBH) of trees and saplings was measured, and soil samples were collected at three depth intervals (0-10 cm, 10-20 cm, and 20-30 cm). Above-ground tree carbon stock was calculated using standard allometric equations, while soil organic carbon (SOC) content was determined using the Walkley-Black method. The total carbon stock was estimated as 179.36 ± 14.29 t/ha, equivalent to 12,126.30 tCO2e/ha. Among the different pools, SOC accounted for the largest share (50.92%) of the total carbon stock and exhibited a consistent decline with depth. The findings suggest that soil constitutes the principal carbon reservoir in community forests, underscoring the role of community forestry in enhancing carbon sequestration and ultimately contributing to climate change mitigation.